Discovery of Quasi‐Stationary Equatorial Waves Trapped in Stratospheric QBO Westerly and Easterly Jets. Issue 1 (30th December 2021) - Sakazaki, Takatoshi; Hamilton, Kevin
Abstract: Quasi‐stationary planetary Rossby waves forced in the extratropical troposphere propagate upwards into the stratospheric vortex and can also be refracted toward the equator. To the extent that such waves penetrate the low latitudes they will be observable as quasi‐stationary zonal eddies in the equatorial middle stratosphere. These eddies should be strongly modulated by the phase of the Quasi‐Biennial Oscillation (QBO) of the mean zonal wind. In this project we used global reanalysis data to examine the quasi‐stationary waves in the monthly mean wind and geopotential fields near the equator and their relation to the QBO mean winds and the extratropical planetary waves. We discovered quasi‐stationary mid‐stratospheric eddy circulations near the equator that often take the form of equatorial planetary modes. Notably a quasi‐stationary equatorial Rossby mode structure can develop during westerly QBO phases, especially when the westerly mean jet is almost symmetric about the equator and deep in the vertical (often in November). More surprisingly, during the easterly QBO phase (EQBO), a modest amplitude quasi‐stationary equatorial Kelvin mode structure develops. Stationary equatorial waves forced in the troposphere will encounter critical surfaces at one or more levels below the mid‐stratosphere, and so presumably cannot account for our findings. A linear, steady model in an equatorial channel that was forced by observed fields specified at extratropical lateral boundaries also cannot fully reproduce the equatorial mode structures, especially for the Kelvin wave during EQBO. Other factors such as transient wave‐mean flow interaction or some dynamic instability might be responsible. Plain Language Summary: We studied the wind at high altitude (∼30 km) during 1979–2019 using recently available representations of the observed atmospheric flow on a fine‐resolution grid over the whole globe. Near the equator we confirmed the expected year‐to‐year variation of the dominant east‐west flow with prevailing easterly winds and prevailing westerly winds alternating in successive years. Contrary to expectations, however, we found that embedded in the prevailing easterly and westerly flow regimes are pressure patterns close to the equator with one high pressure and one low pressure center arranged on opposite sides of the earth. The pressure patterns are accompanied by swirling wind circulations. These patterns are fixed with respect to the ground and can persist for a month or more, but are quite different in the easterly and westerly prevailing wind periods. These patterns are fairly closely trapped near the equator which is somewhat counterintuitive as they may be forced by planetary scale waves originating at higher latitudes. Key Points: Equatorial zonal eddies sometimes take Rossby and Kelvin mode structures in the mid‐stratospheric QBO westerly and easterly, respectively These modes show systematic seasonality and some correlation with the location and strength of planetary waves in the extratropics A simple linear steady‐state model showed only limited success in explaining these modes